Health and burnout of home health care assistants: impact of a training intervention - Saavedra Macías, Francisco Javier; Murvartian, Lara; Vallecillo, Natividad (Anales de Psicología / Annals of Psychology, 2020)
There is a growing need for care in developed countries, so the number of home health care assistants has increased exponentially. The literature has pointed out that this professional group is at high risk for a variety of health problems. Despite its importance, there are no described specific training interventions for it. This study describes a course for a group of female caregivers. A pre-post study is carried out to evaluate its effectiveness considering the following variables: the psychosocial state of health, the burnout and the dysfunctional thoughts about caregiving. The repeated measures ANOVA was used whenever possible and the Wilcoxon-test or the Mann Whitney-test were used as nonparametric tests. Dysfunctional thoughts were reduced after the course, being the effect size medium to large. Social dysfunction was reduced only in the group of women who were also family caregivers. We conclude that professional caregivers can benefit from brief training.